"دور البنوك التجارية في تنويع ومنح القروض - دراسة حالة البنك الوطني الجزائري وكالة الوادي - " - عبد القادر, نيد; عبد الكريم, زندح; ضرار, بالعيدي (جامعة الوادي - University of Eloued, 2023)
"تلعب البنوك التجارية دورا رئيسيا في الاقتصاد الوطني لأي دولة؛ ولقد كان ظهورها بعد أن حصل فائض مالي عند جماعة من الأفراد ووجود عجز مالي لدى الأفراد الأخرين، فكان من وظيفة البنك التدخل کوسيط مالي ما بين هاذين الطرفين ومن بين الوظائف الأساسية للبنوك التجارية نجد: - وظائف كلاسيكية: جمع الودائع ومنح قروض للعملاء. - وظائف حديثة: منها إنشاء النقود، المساهمة في خلق استثمارات جديدة والدخول إلى الأسواق المالية من خلال المضاربة. حيث يهتم البنك بجمع أكبر قدر من الودائع من اجل دعم المركز المالي، كما يعمل جاهدا على توظيف هذه الأموال في منح القروض للعملاء من اجل الحصول على الأرباح التي هي أساس وجوده. أيضا تنويع قروض الاستثمار وقروض التجارة الخارجية وهذا في ظل عولمة مصرفية واسعة لا تؤمن بالحدود وعملياتها في غاية الدقة والشفافية والسرعة في تقديم الخدمة وكذلك يعمل البنك على وضع استراتيجية واضحة التي من خلالها يقوم بدراسة معمقة وكافية وملمة بكل جوانب العميل. " "Commercial banks play a major role in the national economy of any country; And it appeared after a financial surplus occurred with a group of individuals and a financial deficit with other individuals, so it was the job of the bank to intervene as a financial mediator between these two parties, and among the basic functions of commercial banks we find: - Classic functions: collecting deposits and granting loans to clients. - Modern jobs: including creating money, contributing to creating new investments, and entering financial markets through speculation. Where the bank is interested in collecting the largest amount of deposits in order to support the financial position, and it also works hard to employ these funds in granting loans to customers in order to obtain the profits that are the basis of its existence. Also, the diversification of investment loans and foreign trade loans, and this is in light of a wide banking globalization that does not believe in borders and its operations are very accurate, transparent and speedy in providing the service. The bank is also working on developing a clear strategy through which it conducts an in-depth, sufficient and knowledgeable study in all aspects of the customer."
Keywords: البنوك التجارية، التنويع، منح القروض.; Commercial banks, diversification, granting loans.